Mapping Labor Migration Trends Indonesia-Malaysia: Implications for Labor Markets, Remittances, and Bilateral Policies - Sri Damayanti; Yudi Ferdiansyah; Shafira Dita Sasmita (International Publisher (YAPENBI), 2025)
This study analyzes trends in Indonesian labor migration to Malaysia in the last decade, focusing on skill composition, remittance contributions, and policy challenges. The method used is a qualitative approach through literature studies from various official and academic sources. Results show a significant increase in skilled labor migration by 35% since 2015, especially in the technology and health sectors. Real wage differentials between countries are the main driver of migration, with a correlation of 0.8% for every 1% increase in wage differentials. Remittances on average contribute 2.5% to Indonesia's GDP. The study also reveals gaps between policy and factual conditions, especially in the protection of informal workers and women. Using Pierre Bourdieu's theoretical framework, this study emphasizes the importance of social understanding of migration dynamics and the need for more responsive policies.